Impact of Computer Assisted Instruction (CAI) on Teaching and Learning for National Development - DARAMOLA, Florence Olutunu (International Journal of Educational Management, 2021)
Computer-assisted instruction (CAI) is an interactive instructional technique whereby a computer is used to present the instructional material and monitor the learning that takes place. CAI uses a combination of text, graphics, sound and video in enhancing the learning process.Its application in education has made teaching and learning interactive and interesting. However, its usage has been hampered by inadequate facilities and resources. Hence, this paper examined the impact of Computer Assisted Instruction (CAI) and its Relevance to Teaching and Learning for National Development. The meaning of Computer Assisted Instruction and its importance in teaching and learning were investigated and discussed. The advantages and disadvantages of Computer Assisted Instruction in teaching and learning were also highlighted. The study, concluded that Computer Assisted Instruction (CAI) in teaching and learning process will not only facilitate learning but make learning relatively permanent.The study recommended that proper use of CAI can be impactful and relevant in the teaching and learning process for national development.